2021
DOI: 10.1302/1863-2548.15.200084
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric hip ultrasound: Uncertainties in examination and choice of treatment

Abstract: Purpose In Germany, neonates undergo hip sonography examination using the Graf method during the routine U3 screening examination, performed by consultant physicians four to five weeks after birth, and are referred to specialized orthopaedic departments if there are any uncertainties. This study evaluated the quality of sonographic screening in the outpatient sector and the treatment requirements of referred children. Methods We performed a retrospective analysis of the patient data of 384 neonates collected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The extensive demonstration of the validity of the method, as well as the good results in other European countries, makes us select this technique as the most appropriate for our study (12). This screening method is performed in most European centres by trained personnel specialized in traumatology and orthopaedics (13). In our environment, we consider that, since examination and follow-up of the newborn and healthy child is carried out by paediatricians, they are the most suitable for performing the technique and it allows to implement universal screening, without overloading other specialties.…”
Section: Discussionmentioning
confidence: 99%
“…The extensive demonstration of the validity of the method, as well as the good results in other European countries, makes us select this technique as the most appropriate for our study (12). This screening method is performed in most European centres by trained personnel specialized in traumatology and orthopaedics (13). In our environment, we consider that, since examination and follow-up of the newborn and healthy child is carried out by paediatricians, they are the most suitable for performing the technique and it allows to implement universal screening, without overloading other specialties.…”
Section: Discussionmentioning
confidence: 99%
“…The German Association of Statutory Health Insurance Physicians reported that 32% of consultants who applied for initial certification in infant hip sonography did not undertake adequate training [19]. Bucher et al reported that the initial diagnosis at neonatal sonography screening of 132 neonates was confirmed by a certified pediatrician in only 75 cases [20].…”
Section: Discussionmentioning
confidence: 99%